Research on the intersection angle measurement and positioning accuracy of a photoelectric theodolite - Fu, Qiang; Zhao, Feng; Zhu, Rui; Liu, Zhuang; Li, Yingchao (Frontiers in Physics, 2023)
In this paper, a heterogeneous intersection formula, a method of fusion of coordinates, and an error allocation method are introduced in order to improve the target coordinate measurement accuracy of the intersection measurement of the theodolite. Additionally, the angle measurement accuracy of the theodolite is divided into horizontal and vertical components for discussion, and the coordinate measurement accuracy of the theodolite obtained by this method is compared and analyzed. This paper first introduces the formula for coplanar intersection, then suggests the formula for fusing theodolite coordinates and error, and then verifies the accuracy of the formula through experimentation. Finally, it simulates the goniometric accuracy with the normal distribution error using MATLAB and derives the coordinate measurement accuracy using this method. The simulation results demonstrate the viability of the error distribution approach and fusion formula used for data processing in this paper.